1992
DOI: 10.1002/aic.690380510
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of heat transfer in bubbly liquid and liquid‐solid systems: Single bubble injection

Abstract: Local instantaneous changes in heat-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 16 publications
0
41
0
Order By: Relevance
“…Furthermore, within the range of their study ( p / = 1-39 cp), they speculated that this decrease may be caused by the increase in bubble size and rise velocity due to enhanced bubble coalescence with the increase of liquid viscosity which results in decreasing gas holdup and, thereby, heat transfer. However, this explanation is highly suspect as the increased bubble size and rise velocity are reported to increase the local heat transfer (Kumar et al, 1992). Bubble motion and the associated wake flows are believed to be responsible for the above-mentioned transport phenomena in multiphase systems (Fan and Tsuchiya, 1990).…”
Section: Aiche Journalmentioning
confidence: 96%
“…Furthermore, within the range of their study ( p / = 1-39 cp), they speculated that this decrease may be caused by the increase in bubble size and rise velocity due to enhanced bubble coalescence with the increase of liquid viscosity which results in decreasing gas holdup and, thereby, heat transfer. However, this explanation is highly suspect as the increased bubble size and rise velocity are reported to increase the local heat transfer (Kumar et al, 1992). Bubble motion and the associated wake flows are believed to be responsible for the above-mentioned transport phenomena in multiphase systems (Fan and Tsuchiya, 1990).…”
Section: Aiche Journalmentioning
confidence: 96%
“…Two acrylic columns having internal diameters of 25 and 140 mm are used. A rigid borescope [22][23][24][25][26][27][28][29][30][31] (Olympus) with a 60 o field of view and 0 o direction of view is used to obtain particle images in a dynamic system. The borescope has a diameter of 6 mm and length of 250 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Kumar et al (1992) found that the injection of a single bubble into liquids or liquid-solid suspensions enhances the heat transfer rate via bubble wake. Since the wake size is proportional to bubble size, a larger bubble would have a larger wake and stronger vortices associated with the wake, thereby enhancing the rate of heat transfer.…”
Section: Effect Of Pressurementioning
confidence: 99%